2003
DOI: 10.1891/jnum.11.3.225.61275
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaires for the Measurement of Infant Environmental Tobacco Smoke Exposure: A Systematic Review

Abstract: A necessary prerequisite for reducing infant morbidity associated with passive smoking is effective measurement of this health risk factor. The purpose of this review was to evaluate questionnaires currently used in research to measure infant environmental tobacco smoke (ETS) exposure. Systematic searches were conducted using MEDLINE and CINAHL databases to identify current studies of infant ETS exposure. Sixty research reports published between 1996 and 2002 met the selection criteria. All of these investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Most studies attempting to assess children's exposure to ETS only consider exposure from parents due to the relative ease of data acquisition compared to collecting data on ETS that may arise outside of the family unit. It has been shown that the majority of studies to assess adult passive smoking exposure by questionnaire do so in only one or two settings, usually the home and/or workplace [14] but that standard questions to assess where ETS exposure occurs and to what intensity are not available in the adult [14] or child [15] setting. An alternative to questionnaire assessment is the use of a biomarker, in this instance cotinine, a major metabolite of nicotine.…”
Section: Assessing Exposure To Ets In Childrenmentioning
confidence: 99%
“…Most studies attempting to assess children's exposure to ETS only consider exposure from parents due to the relative ease of data acquisition compared to collecting data on ETS that may arise outside of the family unit. It has been shown that the majority of studies to assess adult passive smoking exposure by questionnaire do so in only one or two settings, usually the home and/or workplace [14] but that standard questions to assess where ETS exposure occurs and to what intensity are not available in the adult [14] or child [15] setting. An alternative to questionnaire assessment is the use of a biomarker, in this instance cotinine, a major metabolite of nicotine.…”
Section: Assessing Exposure To Ets In Childrenmentioning
confidence: 99%